The Essential Steps of Medication Administration Practices Project medication administration improvement practices among acute inpatients in a tertiary hospital: a best practice implementation project. Issue 4 (18th December 2020) - Wright, Kylie M.; Bonser, Melissa
ABSTRACT: Objectives: The current project aimed to conduct an audit of nursing medication administration practices, to implement evidence-based best practice recommendations and assess the effectiveness of these changes in maximizing medication administration safety and reducing the risks of adverse incidents across 10 wards/units in a large tertiary hospital. Introduction: Medications are the most common treatment used in healthcare. Because they are so commonly used, medications are associated with a higher incidence of errors and adverse events than other healthcare interventions. Nurses are primarily involved in the administration of medications to patients and this duty is an important aspect of professional practice. The Australian Commission on Safety and Quality in Healthcare has recognized medication safety as a National Standard, thus reinforcing its importance. Methods: The project used the JBI's Practical Application of Clinical Evidence System and Getting Research into Practice audit tool for promoting change in healthcare practice. A baseline audit of 200 observations of medication administration was conducted and measured against eight best practice recommendations, followed by the implementation of targeted strategies and follow-up audits. Results: The baseline audit revealed deficits between current practice and best practice in three of the eight criteria. Identification of barriers for implementation of medication administration best practice criteria were made by the project team and reflective practice and ward/unit led strategies were implemented. There were improved or sustained outcomes across all best practice criteria in the follow-up audits. Conclusion: The findings showed how audit may be used to promote best practice in healthcare and that reflective practice and front-line led strategies can have a positive impact on clinical practice. Some of the measured criteria did not reach 100%, leaving room for improvement; however, by the end of the project attitudes towards medication administration had been 'transformed' from a passive, routine 'must do' task, to an active process with a focus on safety and patient/carer engagement. Future audits are planned to ensure sustainability.